Mitigation of Salinity-Induced Oxidative Damage, Growth, and Yield Reduction in Fine Rice by Sugarcane Press Mud Application - Khan, Imran; Muhammad, Awon; Chattha, Muhammad Umer; Skalicky, Milan; Bilal Chattha, Muhammad; Ahsin Ayub, Muhammad; Rizwan Anwar, Muhammad; Soufan, Walid; Hassan, Muhammad Umair; Rahman, Md Atikur; Brestic, Marian; Zivcak, Marek; et al. (Frontiers in Plant Science, 2022)
Salinity stress is a major abiotic stress that is negatively affecting the crop productivity across the globe. Therefore, it is necessary to find out appropriate ways to reduce the effects of salinity stress on crop productivity for ensuring global food security, Organic amendments possesses an excellent potential to reduce the negative impacts of salinity stress. Sugarcane press mud is an important organic amendment however, its role in mitigating salinity stress in poorly understands. Therefore, this study was performed to determine impact of sugarcane press mud (PM) impacts on growth, yield, physiological attributes, and activities of anti-oxidant enzymes of rice crop grown under salinity stress conditions. The study was composed of different salinity levels control, 6 ds m-1and 12 ds m-1 and different PM levels control, 3%, 6%, and 9%. Salinity stress significantly increased malondialdehyde (MDA; 38%), hydrogen peroxide (H2O2; 74.39%) Na+ (615%) and electrolyte leakage (40.32%), and reduced chlorophyll contents (32.64%), leaf water content (107.77%), total soluble proteins (TSP; 72.28%) and free amino acids (FAA; 75.275) However, these negative impacts of salinity stress were largely reversed in rice plants after the PM application. The application of PM (9%) remained the top performer and it significantly increased to growth, yield, TSP, FAA, accumulation of soluble sugars, proline, K+, and antioxidant enzyme activity including ascorbate peroxidase (APX), catalase (CAT) and peroxidase (POD). Therefore, these findings suggested that application of SPM can be an imperious approach to mitigate the salinity induced oxidative damage, growth and yield reductions in rice crop.